The Influence of Soybean Farmer Characteristics on The Decision To Apply Plant-based Pesticide Technology in Ngaringan District, Grobogan Regency - Dewi, Milinia Sari; Lestari, Eny; Rusdiyana, Eksa (West Science Interdisciplinary Studies, 2024)
Plant-based pesticides are environmentally friendly and sustainable pest control technologies. However, the awareness of soybean farmers in Ngaringan District, Grobogan Regency to apply plant-based pesticides is still low. The low application of plant-based pesticides is influenced by the characteristics of the farmers. This research aims to identify the characteristics of soybean farmers; identify the stages of decision-making among soybean farmers in applying plant-based pesticide technology; and analyze the influence of soybean farmer characteristics on the decision to apply plant-based pesticides in Ngaringan District, Grobogan Regency. The research uses a quantitative method with a survey technique. The research was carried out purposively in Ngaringan District, with a sample of 70 soybean farmers selected through proportional random sampling techniques. Data analysis was conducted using multiple linear regression tests with IBM SPSS Statistics 25. The results of the research show that the majority of soybean farmers in Ngaringan District are in the early elderly age category, very small land areas, formal education at the high school level, very low non-formal education, highly experienced in soybean farming, and high level of cosmopolitanism; the decision-making process for the application of plant-based pesticide technology is categorized as high at the knowledge and persuasion stages, while at the decision, implementation, and confirmation stages, it is categorized as very low; and the farmer characteristics of land area and non-formal education have a significant effect on the decision to apply plant-based pesticides, while age, formal education, farming experience, and cosmopolitanism do not have a significant effect.